Ultrafast wavelength-dependent carrier dynamics related to metastable defects in Cu(In, Ga)Se2 solar cells with chemically deposited Zn(O, S) buffer layer. (August 2020) - Lee, Woo-Jung; Cho, Dae-Hyung; Bae, Jung Min; Kim, Myeong Eon; Park, Jaehun; Chung, Yong-Duck
Abstract: The Cu(In, Ga)Se2 (CIGS) solar cells were fabricated with a Zn(O, S) buffer layer via chemical bath deposition method (CBD) using different thiourea (TU) mole concentration. The solar cells showed a substantial increment in the performance after light soaking treatment for 1 h. The performance increment was found to be in proportion to the TU mole concentration used in Z(O, S) layer deposition. To understand the cause of increased efficiency, we examined the metastable defect states that were reversible and reproducible in the CIGS solar cell. Firstly, to understand the film quality and the interface between CBD-Zn(O, S) and the CIGS layer, chemical states and band alignment along the depth direction was studied from the results of X-ray photoemission spectroscopy (XPS). It was observed that as the TU mole concentration increased, the distribution of S atoms in the CBD-Zn(O, S) layer changed from Gaussian to almost straight line due to the existence of numerous Zn–S bonds at the interface. With the actively diffused S atoms toward CIGS, a hollow band region was formed at the interface of the CIGS/CBD-Zn(O, S) layers, suppressing the electron-hole recombination, and thus enhancing the cell efficiency. Further, to measure the metastable defect states, optical pump-THz probe (OPTP) spectroscopy was utilized with two pumps having beam energies of 400 nm and 800 nm, which were sensitive enough to detect the defect states at an ultrafast time scale. We observed a unique and unusual decay curve of a re-excitation process after the initial ultrafast decay. The decay was contributed by "(VSe –VCu ) divacancy complex, " which is considered a metastable defect state predominantly found near the surface of CIGS layer. The (VSe –VCu ) metastable defect states were filled by photocarriers and then the re-excited photocarriers contributed to the expeditious flow of the photocurrent, giving rise to the increment of the cell efficiency. Graphical abstract: Image 1 Highlights: The CIGS solar cells showed a substantial increment after light soaking treatment. OPTP with two pumps beam energies was used to measure the metastable defect states. Direct correlation between defect states and photocarrier lifetime was verified.